2005
DOI: 10.1007/s11912-005-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib resistance in gastrointestinal stromal tumors

Abstract: Conventional chemotherapeutic drugs are ineffective in treatment of gastrointestinal stromal tumors (GISTs). Imatinib (STI571, Gleevec, Glivec; Novartis Pharmaceuticals, East Hanover, NJ), a selective inhibitor of KIT, ABL, BCR-ABL, PDGFRA, and PDGFRB, represents a new paradigm of targeted cancer therapy and has revolutionized the treatment of patients with chronic myelogenous leukemia and GISTs. Unfortunately, imatinib resistance has emerged. The reported mechanism of imatinib resistance in GISTs involves mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2006
2006
2008
2008

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 30 publications
(22 reference statements)
0
8
0
1
Order By: Relevance
“…Overexpression of BAMBI inhibits the response of tumor cells to TGF-b and suggests that bcatenin interferes with TGF-b-mediated growth arrest by inducing the expression of BAMBI (Sekiya et al, 2004) that may contribute to an invasive GIST phenotype. Acquired mutations leading to IM resistance involve mis-sense mutations in the kinase domain of c-Kit, including Thr670Ile, Tyr823Asp and Val654Ala (Chen et al, 2005;McLean et al, 2005) that are sensitive to PKC412, a novel tyrosine kinase inhibitor (DebiecRychter et al, 2005). A study of 31 GIST patients were treated with IM and then underwent surgery: 13 were sensitive to IM, three had primary resistance and 15 had acquired resistance after initial benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of BAMBI inhibits the response of tumor cells to TGF-b and suggests that bcatenin interferes with TGF-b-mediated growth arrest by inducing the expression of BAMBI (Sekiya et al, 2004) that may contribute to an invasive GIST phenotype. Acquired mutations leading to IM resistance involve mis-sense mutations in the kinase domain of c-Kit, including Thr670Ile, Tyr823Asp and Val654Ala (Chen et al, 2005;McLean et al, 2005) that are sensitive to PKC412, a novel tyrosine kinase inhibitor (DebiecRychter et al, 2005). A study of 31 GIST patients were treated with IM and then underwent surgery: 13 were sensitive to IM, three had primary resistance and 15 had acquired resistance after initial benefit.…”
Section: Discussionmentioning
confidence: 99%
“…66,142 Initial studies showed that secondary KIT mutations occur in the allele that harbors primary gain-offunction KIT mutation and in a great majority of cases represents missense point mutation affecting the first or second tyrosine kinase domain ( Figure 9). 66,89,[143][144][145] Subsequently, polyclonal evolution of multiple secondary KIT mutations has also been reported.…”
Section: Secondary Kit and Pdgfra Mutations Acquired During Imanitib-mentioning
confidence: 99%
“…10,11 Resistance to imatinib has emerged, most commonly because of a new second (or acquired) mutation in the kinase domain. [12][13][14][15][16] GISTs show a predilection for liver metastasis and peritoneal implants-in vivo clones, and therefore provide an excellent model for studying the tumor biology. The histologic types of GISTs vary from very low grade to highly aggressive, and mitotic count vary more than 20-fold, To understand tumor progression, longitudinal follow-up of clonal evolution and comparison of primary tumor and subsequent recurrences within the same patient is probably the best means of circumventing both the interpatient variations and the complex events associated with late-stage advanced tumor progression.…”
mentioning
confidence: 99%